(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
This article explores the diverse factors influencing the psychological development of preschool-aged children, emphasizing the importance of early experiences, social interactions, parental influence, environmental factors, and professional support. It discusses the interconnectedness of these elements and their role in shaping emotional intelligence, cognitive abilities, and resilience in young minds.